Evaluation of llama anti-botulinum toxin Heavy chain Antibody. (26th June 2008) - Anderson, George P.; Ortiz-Vera, Yakelin A.; Hayhurst, Andrew; Czarnecki, Jill; Dabbs, Jason; Vo, BaoHan; Goldman, Ellen
Lama immunoglobulins consist of conventional antibody (IgG1) and unique forms that lack light chains, called heavy chain antibodies (IgG2 and IgG3). These unusual antibodies possess unique properties ideal for diagnostics and therapeutics. To evaluate the IgG from a llama immunised with botulinum complex toxoids A through F each IgG subclass was tested as capture and recognition ligand in xMAP fluid array immunoassays. The optimal combination, IgG3 capture and IgG2 tracer, detected as low as 64 pg/ml of BoNT/A complex toxoid. Also, heavy chain antibodies were shown to bind BoNT as effectively as conventional IgG1, while possessing much greater thermal stability. [Received 15 October; Accepted 28 December 2007]